INDIVIDUAL STYLE OF PROFESSIONAL ACTIVITY OF FUTURE PSYCHOLOGISTS: ESSENCE AND WAYS OF FORMATION IN THE EDUCATIONAL PROCESS OF A HIGHER EDUCATION INSTITUTION - Volkova Nataliia; Bykova Viktoriia (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The article examines the problem of the individual style of professional activity of future psychologists. The purpose of the article is to substantiate the essence, the component composition of the individual style of professional activity of future psychologists, the ways of its formation in terms of the educational environment of a higher education institution. It has been shown that an individual style is a factor of professional success, and therefore the specificity of its formation depends on the type of professional activity. The stages of formation of an individual style of activity have been specified. It covers, firstly, the development of professional activity with already worked out schemes and procedures, and secondly, the deviation from normatively approved work samples. The individual style of professional activity of future psychologists is presented as an integral personal formation that determines the individual strategy and tactics of organizing psychological activity and ensures productivity and optimal solution of professional tasks. The components of the individual style of professional activity of future psychologists have been defined. The content of the individual style of future psychologists’ professional activity includes motivational-value (a system of motives, and value attitudes); cognitive (a set of knowledge about the essence and structure of the individual style of professional activity of future psychologists, ways of its formation); personal-active (methods, techniques, procedures, productive technologies, and tools of implementing psychological knowledge in work by specialities); reflective-evaluative components (an ability to professional and personal reflective). It has been emphasized that the individual style of professional activity is not formed by itself, but requires painstaking and systematic work on oneself, performing the function of adaptation to the requirements of professional activity and is a system of individually unique methods that ensure successful performance of the work of a practical psychologist. The methodological aspects of the formation of the individual style of professional activity of future psychologists have been identified. It is a set of systemic, functional, synergistic, axiological, and personally oriented approaches. It has been substantiated that the formation of the individual style of professional activity of future psychologists requires the modelling of the content of each educational component of the educational program in the specialty 053 Psychology according to the logic of the tasks of future professional activity; the use of practically oriented learning technologies (dialogic-discussion, game, training, project, and case ones, as well as training, exercises, web quests, webinars, workshops, etc.). Emphasis is placed on the need to involve students in various practical activities for the implementation of professional initiatives in cooperation with partners of higher education institutions and employers. An interesting experience of acquiring personal professional experience by future psychologists through involvement in end-to-end practice, in particular the practice of the “Supervision Studio”, has been revealed. The prospect of further research is found in the study of the problems of organizing the self-educational activities of future psychologists for the development of the individual style of professional activity